2019
DOI: 10.3389/fcvm.2019.00106
|View full text |Cite
|
Sign up to set email alerts
|

RNAs and RNA-Binding Proteins in Immuno-Metabolic Homeostasis and Diseases

Abstract: The increasing prevalence of worldwide obesity has emerged as a major risk factor for type 2 diabetes (T2D), hepatosteatosis, and cardiovascular disease. Accumulating evidence indicates that obesity has strong inflammatory underpinnings tightly linked to the development of metabolic diseases. However, the molecular mechanisms by which obesity induces aberrant inflammation associated with metabolic diseases are not yet clearly defined. Recently, RNAs have emerged as important regulators of stress responses and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 226 publications
(215 reference statements)
0
24
0
Order By: Relevance
“…We have summarized the classical as well as emerging hallmark functions of RBPs in Figure 1. Given their widespread impact on gene expression and signaling networks, mutations or defects in the expression or localization of RBPs can cause a broad range of diseases, e.g., neurodegeneration, obesity, hypertension, and cancer [55,[89][90][91][92][93][94][95][96]. In the next paragraph, we will highlight selected examples of RBPs that have been shown to contribute to the malignancy of oral cancer, especially its metastatic features.…”
Section: General Functions and Mechanisms Of Rna-binding Proteinsmentioning
confidence: 99%
“…We have summarized the classical as well as emerging hallmark functions of RBPs in Figure 1. Given their widespread impact on gene expression and signaling networks, mutations or defects in the expression or localization of RBPs can cause a broad range of diseases, e.g., neurodegeneration, obesity, hypertension, and cancer [55,[89][90][91][92][93][94][95][96]. In the next paragraph, we will highlight selected examples of RBPs that have been shown to contribute to the malignancy of oral cancer, especially its metastatic features.…”
Section: General Functions and Mechanisms Of Rna-binding Proteinsmentioning
confidence: 99%
“…This is probably what occurs in asymptomatic individuals who can establish an effective response against SARS-CoV-2 (9, 141). However, in several viruses, viral proteins can modulate the production of this type of IFN, impairing the generation of an effective antiviral response (141,143,146,147). Li et al (148) conducted an in vitro experiment that revealed a strong capacity of ORF6, ORF8, and nucleocapsid proteins of SARS-CoV-2 to inhibit IFN-b and NF-kB activity, in addition to genes containing interferonstimulated response elements (ISREs), suggesting that the virus has an important IFN antagonist activity.…”
Section: Immune Response Against Sars-cov-2 Cytokine Stormmentioning
confidence: 99%
“…Among the non‐coding RNAs, it is possible to distinguish two subclasses: small non‐coding RNAs, molecules smaller than 200 bp, and lncRNAs, defined as non‐coding RNA molecules longer than 200 bp 22 . LncRNAs are poorly conserved, frequently unstable, and/or sometimes present in few copies, and new biological roles have emerged for some lncRNAs 23–25 . In order to facilitate the reader through this mounting evidence in different models, the lncRNAs reported in this work are listed for their homology as summarized in Table S1.…”
Section: Lncrnas: Definition and Principal Functionsmentioning
confidence: 99%